KESEIMBANGAN ALAM DALAM PERSPEKTIF SCEINTIA SACRA SEYYED HOSSEIN NASR - Arif Syafi'uddin (UIN Sunan Kalijaga Yogyakarta, 2014)
Sacred science or scientia sacra in latin from Nasr, as exposed in this article refers to the application of sacred knowledge to various domain of reality, both physical and spiritual. Any science, be it natural, mathematical or intellectual, that places the sacred at the center of its structure is sacred, to the extent that it is an application of the immutable principles of metaphysics to the world of change and relativity. It is based on a worldview that considers nature, the very subject matter of science, as a sacred being, vestigia dei, ayatollah, or the signs of God which point to the symbolic significance of the world of nature. In contrast with the view of modem science that reduces the order of nature to everlasting change and impermanence. One can also say that sacred science is the real continuation of traditional sciences, such as Islamic science and medieval, depends on its metaphysical roots.